Animer l’espace public ? Une question pluridisciplinaire de recherche - Pascale Pichon; Jean-Paul Thibaud (Ambiances)
The animation of public spaces is the central theme of this special issue of the Ambiances journal. It deals with the articulation of places and temporalities that stages a plurality of actions and actors. The contributions that compose this issue come from different disciplines: architecture, art, sociology, geography, political science. It opens a dialogue between various situations and investigation procedures. The fabric of city life is thus enlightened, as are the consequences of this “activation” of our ways of life, and its impact on the quality of urban life. Three main lines cross all the contributions, making it possible to update the stakes of such a theme. First, the animation leads to questioning the socio-aesthetic part of the living experiences and urban processes at work. Secondly, animation needs to be questioned in its historical, anthropological and phenomenological depth. Thirdly, the animation is based on political issues of the utmost importance and calls for a critical and attentive look at its effects.